Gender Dysphoria, issues and solutions - Said, Abdul Hadi (Kulliyyah of Medicine, IIUM, 2023)
Gender dysphoria has long been discussed in all parts of the world. Everyone has an opinion on this subject. The most important thing, though, is to discover the finest answer to it. Some may take a different strategy than others, which is entirely dependent on personal preferences. This book examines the subject from the eyes of Muslim researchers at IIUM University. Not only are we debating the problem, but we are also proposing a solution that we believe is the best way to tackle it. This book explains the fundamentals of gender dysphoria, its health difficulties, the fundamentals of normal sexual physiology, and our strategy for working with this population. Hopefully, this book will benefit many researchers and academicians out there to better understand this topic and join us in dealing with the community together in the future.